Minimizing The Development of Lake at River Meeting Points to Reduce Floods in Jakarta Using the Dominating Set Application - Muhlisatul Mahmudah (Universitas Islam Jember, 2019)
One of the theories developed in graph theory is the dominating set. Dominating set is a concept of determining the minimum point on the graph with the provision of a point as dominating set to reach the point that is around it. The smallest cardinality of the dominating set is called the domination number denoted by (G). Given graph G with point V and E side, let D be a subset of V. If each point of VD is adjacent at least one point from D, then D is said dominating set in graph G. Currently a lot of applications from dominating set, one of which is Minimizing the Construction of Lakes at River Meeting Points to Reduce Floods in Jakarta. In this study a river meeting will be rebuilt to select floods in Jakarta. Flooding is a natural disaster which is currently often in Indonesia. Especially in Jakarta. Jakarta is one of the risk areas for flooding in Indonesia and floods that always occur suddenly There are so many ways to reduce them, but that doesn't work. One of the causes of flooding in Jakarta is the overflow of river air. When a patient appears suddenly several rivers that have large currents, air flow will collide at the meeting point. When the river flows, the air will overflow large enough. Therefore, it is important to develop a lake at the river meeting point but it is necessary to make the lake as minimal as possible and also to be efficient. The research application dominates the set of lake developments in each river meeting point in the city. Keywords: dominating set, river, flood